(Re)negotiating authenticity through virtual travel: a case study of Law of the Jungle, a Korean reality travel program. Issue 3 (24th March 2018) - Kim, Sohye; Park, Sanghun; Santos, Carla A.; Shinew, Kimberly J.
ABSTRACT: The current study investigates tourists' discourse regarding authenticity in the postmodern tourism context by employing the intertwined concepts of authenticity and gaze to examine Law of the Jungle, a Korean reality travel program. Findings from our thematic content analysis of data suggest that the program provides viewers with a dual structure through which to view and negotiate the tourism setting of the show, and that the authenticity of the program is perceived from three main perspectives: objective, subjective, and postmodernist. Findings are contextualized within extant literature on authenticity, orientalism, the tourist gaze, and the second gaze.